2002
DOI: 10.2355/isijinternational.42.534
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Native Rust Layer Formed on a Low Alloy Steel Exposed in Marine Atmosphere.

Abstract: Low alloy steel panels, exposed in marine atmosphere for 4 years, formed a compacted rust layer which could suppress the penetration of corrosive electrolyte and lower the corrosion rate. But in practical applications, the protective reliability is limited by the mechanical properties of the rust layer under the action of various loads. This paper presented the first attempt to evaluate the variation of mechanical properties of the protective rust layer with the exposure term by means of micro-indentation test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…4). Zhang et al [177] confirmed in the marine atmosphere of Quingdao (35 mg Cl -/m 2 day) the results obtained by Larrabee and Coburn. The thickness loss of steels exposed in marine atmosphere decreased rapidly as their Cr content was increased.…”
Section: Chromium Steelssupporting
confidence: 58%
“…4). Zhang et al [177] confirmed in the marine atmosphere of Quingdao (35 mg Cl -/m 2 day) the results obtained by Larrabee and Coburn. The thickness loss of steels exposed in marine atmosphere decreased rapidly as their Cr content was increased.…”
Section: Chromium Steelssupporting
confidence: 58%
“…For samples with the tensile residual stress region of 13 000 × 10 000 × 350 μm 3 , when the corrosion depth was only 2 μm, the variation of residual stress distribution caused by the curvature of 1.6 × 10 -5 could be ignored. Considering plastic deformation energy approximates to zero for iron oxides, 34) the possibility of prevention of tensile stress by bending deformation in the rust layers can be ignored. In this case, the rust layer will deform with the steel matrix when the rust layer is well combined with the steel matrix.…”
Section: Rust Layer Analysismentioning
confidence: 99%
“…where, a is the crack length, c σ is the critical fracture stress, and c K is the critical fracture toughness of the rust. From Ouglova et al [Ouglova, Berthaud, Francois et al (2006); Zhang, Ma, Wu et al (2002)], Kc=2.60 MPa•m 0.5 , a =3.35 µm. Therefore, σc is calculated as 802 MPa.…”
Section: Figure 1: Fe Modelmentioning
confidence: 99%
“…From the literature [Zhang, Ma, Wu et al (2002)], 28 KIC=2.60 MPa• 0.5 m . Therefore, Gc is estimated as 506 N/m.…”
Section: Figure 1: Fe Modelmentioning
confidence: 99%